Integrating a Tropos Modeling Tool with a MDA Methodology for Engineering Multi-agent Systems - Guinelli, João Victor; Pantoja, Carlos Eduardo; Choren, Ricardo (Anais do Workshop-Escola de Sistemas de Agentes, seus Ambientes e Aplicações (WESAAC), 2015)
This paper presents an integration between a Model-Driven Architecture (MDA) methodology for Multi-Agent System (MAS) development and the TAOM4E, which is a tool for graphical modeling that gives support to the Tropos methodology. Additionally, the MDA methodology uses the FAML, which is a metamodel that includes concepts of several agent-oriented methodologies (including Tropos) into a single model as Platform Independent Model and the JaCaMo metamodel, composed of Jason, Moise+ and CArtAgO, as Platform Specific Model. The methodology is also able to transform FAML concepts to JaCaMo concepts and generate code to the Jason/Moise+ from JaCaMo metamodel. The objective of this is paper is to allow the MAS designer to generate Jason/Moise+ code directly from a Tropos model using the proposed integration. The transformation set between the graphical modeling tool and the FAML metamodel was specified using the Query-View-Transformation language. The paper also presents an example using the integrated solution.